Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran IPAS dengan Menggunakan Model Cooperative Learning Tipe Auditory Intellectually Repetition (AIR) di Kelas IV SDN 03 Geragahan Kabupaten Agam - Gultom, Lisa Novianti; Zuardi, Zuardi (TSAQOFAH, 2025)
The low learning outcomes of students served as the background of this study, particularly in the IPAS subject on the topic Landscapes and Their Utilization in Relation to Professions in Grade IV at SDN 03 Geragahan, Agam Regency. The aim of this research is to describe the improvement in learning outcomes through the implementation of the Cooperative Learning model of the Auditory Intellectually Repetition (AIR) type. This study is a Classroom Action Research (CAR) employing both quantitative and qualitative approaches, conducted over two cycles. The research subjects included 24 students, the classroom teacher as an observer, and the researcher as the practitioner. The findings show significant improvements across various aspects: the average score of teaching module assessments increased from 85.4% in cycle I to 95.83% in cycle II; teacher activity rose from 82.75% to 96.87%; student activity also improved from 82.75% to 96.87%; and the average student learning outcomes increased from 71.4% to 87.81%. These results demonstrate that the AIR Cooperative Learning model fosters an active, collaborative, and reflective learning environment, leading to a positive impact on learning outcomes. In conclusion, the AIR model is effective as a learning strategy for improving IPAS learning outcomes in primary education.